Glycyrrhizic acid modified Poria cocos polyscaccharide carbon dots dissolving microneedles for methotrexate delivery to treat rheumatoid arthritis - Chen, Qi; Wu, Chengyuan; Wang, Siwei; Wang, Qiang; Wu, Peiyun; Wang, Lei; Yan, Peiyu; Xie, Ying (Frontiers in Chemistry, 2023)
Introduction: Rheumatoid arthritis is an autoimmune disease characterized by chronic joint inflammation. Methotrexate is one of the most effective drugs for rheumatoid arthritis, but the adverse reactions caused by oral methotrexate greatly limit its clinical application. Transdermal drug delivery system is an ideal alternative to oral methotrexate by absorbing drugs into the human body through the skin. However, methotrexate in the existing methotrexate microneedles is mostly used alone, and there are few reports of combined use with other anti-inflammatory drugs. Methods: In this study, glycyrrhizic acid was first modified onto carbon dots, and then methotrexate was loaded to construct a nano-drug delivery system with fluorescence and dual anti-inflammatory effects. Then hyaluronic acid was combined with nano-drug delivery system to prepare biodegradable soluble microneedles for transdermal drug delivery of rheumatoid arthritis. The prepared nano-drug delivery system was characterized by transmission electron microscopy, fluorescence spectroscopy, laser nanoparticle size analyzer, ultraviolet-visible absorption spectroscopy, Fourier transform infrared spectroscopy, differential scanning calorimeter and nuclear magnetic resonance spectrometer. The results showed that glycyrrhizic acid and methotrexate were successfully loaded on carbon dots, and the drug loading of methotrexate was 49.09%. The inflammatory cell model was constructed by lipopolysaccharide-induced RAW264.7 cells. In vitro cell experiments were used to explore the inhibitory effect of the constructed nano-drug delivery system on the secretion of inflammatory factors by macrophages and the cell imaging ability. The drug loading, skin penetration ability, in vitro transdermal delivery and in vivo dissolution characteristics of the prepared microneedles were investigated. The rat model of rheumatoid arthritis was induced by Freund's complete adjuvant. Results: The results of in vivo animal experiments showed that the soluble microneedles of the nano drug delivery system designed and prepared in this study could significantly inhibit the secretion of pro-inflammatory cytokines and had a significant therapeutic effect on arthritis. Discussion: The prepared glycyrrhizic acid-carbon dots-methotrexate soluble microneedle provides a feasible solution for the treatment of Rheumatoid arthritis.